RARE EARTH ELEMENT EVOLUTION OF PHANEROZOIC SEAWATER RECORDED IN BIOGENIC APATITES - Lécuyer C.; Reynard B.; Grandjean P. (My University, 2004)
Rare earth element (REE) contents of marine biogenic apatites have been shown to record seawater compositions. A data base of available and newly acquired rare earth element (REE) contents of marine biogenic apatites has been created to assess the past seawater REE compositions. To ensure that this data base contains only the pristine REE signals, altered samples, characterized by very low (La/Sm)N ratios (where N stands for REE ratios normalized to the NASC composition; Gromet et al., 1984, Geochim. Cosmochim. Acta 48 (1984) 2469) acquired during apatite recrystallization, are not included in the database. These data reveal a change in the Tethyan seawater composition between 110 and 80 Ma. After the end of the Cretaceous, the REE chemistry of seawater remains constant until present-day. This seawater composition change is likely due to concurrent changes in REE scavenging processes. A strong correlation between decreasing (Sm/Yb)N ratios and increasing Ce anomalies for samples deposited during the 80–110 Ma period is observed. As Ce anomalies are attributed to ocean water redox conditions, changes in REE scavenging could reflect an evolution from stratified and poorly oxygenated waters towards well-mixed and oxygenated waters. This could have resulted from changing current patterns stemming from the contemporaneous opening of the Atlantic Ocean. A major change in Middle and Late Cretaceous oceanic circulation linked to plate tectonics would have favored the colonization of pelagic environments.